2012
DOI: 10.12659/msm.883353
|View full text |Cite
|
Sign up to set email alerts
|

In vivo influence of extract from Aronia melanocarpa on the erythrocyte membranes in patients with hypercholesterolemia

Abstract: SummaryBackgroundHypercholesterolemia increases cholesterol concentration in erythrocyte membranes, which results in decrease of membrane fluidity and decreases the deformability of red blood cells. The fruits of Arona melanocarpa contains many of polyphenols and other compounds that have beneficial health effects.Material/MethodsThe aim of the study was to estimate the influence of 2-month supplementation of extract from Aronia melanocarpa (100 mg Aronox, three times per day) on cholesterol concentration, lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 47 publications
(52 reference statements)
3
26
0
Order By: Relevance
“…Beneficial changes in coagulation indices (reduction in adenosine diphosphate-induced clot formation and inhibition of the amidolytic activities of both thrombin and plasmin) were also observed (Sikora et al, 2012;Sikora et al, 2014a). In accordance with this, an improvement of the rheological properties of erythrocytes was shown in hypercholesterolemic patients receiving 300-mg Aronox R over 2 months (Duchnowicz et al, 2012). The exact mechanism of action has not yet been elucidated, but it is agreed that the radical-scavenging effect contributes to the improvement of metabolic syndrome disorders (Keaney et al, 2003;Kardum et al, 2014).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Beneficial changes in coagulation indices (reduction in adenosine diphosphate-induced clot formation and inhibition of the amidolytic activities of both thrombin and plasmin) were also observed (Sikora et al, 2012;Sikora et al, 2014a). In accordance with this, an improvement of the rheological properties of erythrocytes was shown in hypercholesterolemic patients receiving 300-mg Aronox R over 2 months (Duchnowicz et al, 2012). The exact mechanism of action has not yet been elucidated, but it is agreed that the radical-scavenging effect contributes to the improvement of metabolic syndrome disorders (Keaney et al, 2003;Kardum et al, 2014).…”
Section: Discussionsupporting
confidence: 70%
“…Beneficial changes in coagulation indices (reduction in adenosine diphosphate‐induced clot formation and inhibition of the amidolytic activities of both thrombin and plasmin) were also observed (Sikora et al ., ; Sikora et al ., ). In accordance with this, an improvement of the rheological properties of erythrocytes was shown in hypercholesterolemic patients receiving 300‐mg Aronox R over 2 months (Duchnowicz et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Oxysterol toxicity at endothelial cells and macrophages has been involved in the pathogenesis of atherosclerosis and cardiovascular diseases [1]. It is interesting to mention that RBCs from hyper-cholesterolemic patients show higher levels of oxidized lipids and lower concentration of membrane protein thiols than healthy RBCs [72], which could be an indication of the oxysterol toxicity and proneness of cholesterolemic RBCs to eryptosis. Since PS-exposing RBCs can adhere to vascular endothelial cells [25,27] impairing microcirculation, and possess pro-thrombotic and blood clotting activity [23,24], our study suggests that the eryptotic activity of oxysterols can also contribute to development of atherosclerosis and ischemic problems associated with hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…10,27,35 Contrary to the reported studies involving subjects with mild hypercholesterolemia or metabolic syndrome, participants involved in our study were apparently healthy. The values of biochemical parameters, recognized as traditional risk factors for CVD, were in reference intervals at the beginning as well as at the end of the study.…”
Section: Discussionmentioning
confidence: 83%
“…Still, this is in accordance with the results of a recent study showing that neither one-nor two-month-long supplementation with chokeberry extract had statistically significant influence on thiol groups' levels in erythrocyte membranes. 27 In a recent in vitro study, chokeberry extract was also found to be ineffective in modulation of thiol levels in plasma obtained from healthy subjects. 28 Human paraoxonase (PON1) is polymorphic, highdensity lipoprotein (HDL) associated esterase.…”
Section: Discussionmentioning
confidence: 99%